Gambaran Multidimensi Partisipasi Politik Masyarakat di Kabupaten Bondowoso - Haressa Lintang Rizkika; Zainul Mukid; Muhammady Iffan Gallant El (SS&H: Studies in Social Sciences and Humanities, 2025)
This study aims to describe the multidimensional level of political participation among the people of Bondowoso Regency. Data were collected from 92 respondents who met the criteria of being Bondowoso residents and having participated in political activities, particularly elections. The indicators of political participation examined in this study include trust, awareness, knowledge, and active engagement in political processes. To ensure the reliability and validity of the findings, a previously validated political participation measurement tool was adopted. This instrument was adapted from prior research on political participation in Indonesia, with adjustments made to fit the local context of Bondowoso. Descriptive analysis results indicate that the majority of respondents exhibit low to moderate levels of political trust, while their political knowledge generally falls within the moderate category. The study also reveals that despite having a relatively good level of political awareness, this alone is insufficient to foster more active political participation without strong trust in political institutions. Nevertheless, this study has several limitations, including a relatively small sample size and potential bias in the measurement instruments. Future research is recommended to expand the sample size, develop more robust measurement tools, and consider broader contextual factors to gain deeper insights into the dynamics of political participation and public perceptions of local political processes.